Novel pathogenic variant in a mild case of type B molybdenum cofactor deficiency: case report and literature review - Morgan Kinsinger; Jelena Ivanisevic; Divakar S. Mithal (BMC Medical Genomics)
Abstract Background Molybdenum cofactor deficiency (MoCD) is a rare metabolic disorder caused by pathogenic variants in the highly conserved biosynthetic pathway of molybdenum cofactor (MoCo), resulting in sulfite intoxication. MoCD may present in a clinically severe, fatal form marked by intractable seizures after birth, hyperekplexia, microcephaly and cerebral atrophy, or a later onset form with a more varied clinical course. Three types of MoCD have been described based on the effected gene along the MoCo synthesis pathway: type A (MOCS1); type B (MOCS2 or MOCS3) and type C (GPHN). The MOCS2 gene is bicistronic, encoding the small (MOCS2A) and large (MOCS2B) subunits with an overlapping coding region. This case report describes a patient with the first known variant causative of mild disease in the overlapping bicistronic region (c.263 G > C) and the first ever described in the highly conserved C-terminal glycine-glycine motif of MOCS2A. Case presentation The patient developed normally until age 12 months when she presented in the setting of acute illness with developmental regression, low serum uric acid, and MRI with bilateral globus pallidus (GP) injury. Exome sequencing identified a homozygous variant of unknown significance in the MOCS2 gene and the diagnosis of MoCD type B was confirmed by the patient’s low serum uric acid coupled with elevated urine sulfocysteine and associated metabolites, resulting in gene reclassification. Nearly four years after her initial presentation she has demonstrated progress in language and motor domains, consistent with a mild phenotype of MoCD. Conclusions The case emphasizes challenges in identifying atypical forms of rare diseases, the importance of exome sequencing to identify mild cases of MoCD, and the ongoing challenges with understanding the MOCS2 gene. While one FDA approved treatment exists for MoCD type A, further research into the mechanisms of phenotype-genotype differences among this patient population may aid in additional therapeutic options for MoCD.